HUBUNGAN PENGETAHUAN PATIENT SAFETY DENGAN KEPATUHAN PENERAPAN (SURGICAL SAFETY CHECKLIST) - Dwi sari; Dwi Soelistyoningsih; Frengki Apryanto (Jurnal Keperawatan dan Kesehatan Masyarakat Cendekia Utama, 2023)
Background: Surgical Safety Checklist (SSC) is used in the operating room to increase the safety of surgery and reduce errors in surgical procedures. The low level of compliance in filling out the SSC has the potential to cause problems related to patient safety which are influenced by knowledge related to patient safety. Objective: The aims of this study was to examine the correlation between the level of knowledge of patient safety with nurse compliance in the application of filling the Surgical Safety Checklist (SSC). Method: Research design was correlational quantitative with cross sectional approach and analytic observational method. The sample of nurses in the operating room was 30 respondents. The sampling technique was non-probability sampling with a total sampling approach. The instruments used were a patient safety knowledge questionnaire and a surgical safety checklist. The statistical test used in this study was the calculation of Fisher Exact. Results: The results of the research indicated 23 respondents (76.7%) had knowledge about patient safety in good category, while 22 respondents (73.3%) had compliance in the application of SSC. The results of the analysis using the Fisher Exact correlation calculation indicated p value = 0.000. Conclusion: Based on the results of the study, it is concluded that there is a significant correlation between the level of knowledge of patient safety and nurse compliance in the application of SSC (surgical safety checklist) in the operating room of  Permata Bunda Hospital, Malang.